National and provincial prevalence of self-reported diabetes: results from the cross-sectional Demographic and Health Survey in Sri Lanka–2016 - Sobha Sivaprasad; Manjula D Nugawela; Harshana Munasinghe; Pansujee Dissanayaka; Mangalika Jayasundara (BMJ Public Health)
Introduction Diabetes is a major global public health burden. The objective of this study was to estimate the national and provincial-level prevalence of self-reported diabetes and establish the demographic risk factors of diabetes in Sri Lanka.Research design and methods A nationally representative sample of the population from all nine provinces in Sri Lanka was obtained from the cross-sectional Demographic and Health Survey 2016. Those aged 20 years and older were included in this study. Age, sex, ethnicity, religion, education level, marital status, sector of the resident (urban/rural/estate) and province of residence were included as potential exposures. The outcome was defined as self-reported diabetes.Results The age-adjusted national prevalence of self-reported diabetes was 10.60% (95% CI: 10.59% to 10.602%). Provinces with higher gross domestic product (GDP) per capita showed a higher prevalence of diabetes. The Western province with the highest GDP of 734 094 Sri Lankan rupee showed the highest prevalence of diabetes (13.3%; 95% CI: 13.32% to 13.34%) compared with 8.1% (95% CI: 8.54% to 8.58%) in the Northern province with lowest GDP (321 289 Sri Lankan rupee). Prevalence of diabetes was higher among residents living in urban areas (14.39%; 95% CI: 13.72% to 15.06%) compared with their counterpart. Other risk factors of self-reported diabetes included age, gender, ethnicity, education level and marital status with those aged 55–64 years, females, who belong to Moor ethnicity, had secondary or higher education, and divorced or widowed had higher risk of diabetes compared with their counterparts.Conclusions Sri Lanka has a high prevalence of self-reported diabetes and it differs by province, sector of residence, sex, education level, ethnicity, age and marital status. There is a need for risk stratifying adult Sri Lankan population to help target those at high risk of diabetes so that cost-effective approaches of screening, preventive and treatment options can be initiated.